Analisis Homo Deus Dalam Pandangan Harari serta Fakta Kemajuan Teknologi Di Era Society 5.0 - Mitha Mayestika Kuen; Hafied Cangara; Hasrullah Hasrullah (Al-MUNZIR, 2022)
Yuval Noah Harari, a historian from the Hebrew University of Jerusalem, has produced works that have become the subject of discussion in the public sphere. The work is Homo Deus (2015) trying to explain "Where is human civilization going". A fairly simple but basic question about humans and their civilization is posed by Harari in the book. including: how the impact of human life on other creatures? Where will technological developments take us? Homodeus' book review will be described using the critical discourse analysis method of Van Dijk, Fairclough and Wodak who say that critical discourse analysis includes context within the scope of background, situation, history, power, and ideology. to a data religion called Harari. Only a handful of people evolved into Homo Deus, while most remained Homo Sapiens because they were unable to access future cutting-edge technology. The thing to watch out for is the emergence of dependence and addiction to super-intelligent technology that can amputate basic human abilities themselves. Thus, intelligent technology is no longer merely a subject, but also an object that extends human intelligent abilities. Therefore, a smart human role is needed in society 5.0 that selects and sorts out super-intelligent technology for the common good.Keywords: Homo Deus, Technological Facts, Society 5.0